2011
DOI: 10.5402/2011/301490
|View full text |Cite
|
Sign up to set email alerts
|

Novel Vitamin D Analogs for Prostate Cancer Therapy

Abstract: Prostate cells contain specific receptors for 1α,25-dihydroxyvitamin D [1α,25(OH)2D] or calcitriol, the active form of vitamin D. 1α,25(OH)2D is known to inhibit the proliferation and invasiveness of prostate cancer cells. These findings support the use of 1α,25(OH)2D for prostate cancer therapy. However, 1α,25(OH)2D can cause hypercalcemia, analogs of 1α,25(OH)2D that are less calcemic but exhibit potent antiproliferative activity would be attractive as therapeutic agents. To accomplish these goals, different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…These investigations have shown that both analogues possess antiproliferative activity comparable with that of 1,25(OH) 2 D 3 . However, MART-10 proves about 1000-fold more active than 1a,25(OH) 2 D 3 in inhibiting LNCaP and PC-3 prostate cancer cell proliferation (Chen & Kittaka, 2011;Iglesias-Gato et al, 2011). Furthermore, in vitro studies which compared the expression level of the enzyme CYP24A1 in LNCaP and PC-3 in response to treatment with 1,25(OH) 2 D 3 and MART-10 showed that this latter molecule was able to induce the expression of CYP24A1, one of the three major enzymes involved in the metabolism of Vit D (Jones et al, 2012), to a lower concentration than calcitriol (Flanagan et al, 2009).…”
Section: Mart-10 Mart-11mentioning
confidence: 95%
See 4 more Smart Citations
“…These investigations have shown that both analogues possess antiproliferative activity comparable with that of 1,25(OH) 2 D 3 . However, MART-10 proves about 1000-fold more active than 1a,25(OH) 2 D 3 in inhibiting LNCaP and PC-3 prostate cancer cell proliferation (Chen & Kittaka, 2011;Iglesias-Gato et al, 2011). Furthermore, in vitro studies which compared the expression level of the enzyme CYP24A1 in LNCaP and PC-3 in response to treatment with 1,25(OH) 2 D 3 and MART-10 showed that this latter molecule was able to induce the expression of CYP24A1, one of the three major enzymes involved in the metabolism of Vit D (Jones et al, 2012), to a lower concentration than calcitriol (Flanagan et al, 2009).…”
Section: Mart-10 Mart-11mentioning
confidence: 95%
“…However, the hypercalcemic effects induced by 1,25(OH) 2 D 3 have strongly limited its therapeutic use Mehta, 2012). Therefore, many efforts are currently being directed towards synthesizing new Vit D analogues with the goal of improving the biological profile of the natural hormone, which retains the therapeutic activity the analogues being endowed with a lower calcemic effect (Byers et al, 2012;Chen & Kittaka, 2011;Fleet et al, 2012;Trump et al, 2010). Vit D analogues are semi-synthetic molecules, since they share the basic structure of 1,25(OH) 2 D 3 but differ in the presence of a characteristic functional group (R) (Brown & Slatopolsky, 2008;Trump et al, 2010;Unten et al, 2004) (Figure 2).…”
Section: Effects Of Malignant Transformation On 1-a-hydroxylase (Cyp2mentioning
confidence: 99%
See 3 more Smart Citations